A study of the preliminary National Forest Inventory in Georgia : with special emphasis on degraded vs. non-degraded forest - Beil, Rahel (SLU/Southern Swedish Forest Research Centre, 2019)
The South Caucasus and particularly Georgia are known as a “biodiversity hotspot” because of their unique flora and fauna which holds an outstanding amount of endemic species. Knowing this flora and fauna is crucial to protect it, but also to manage the natural resources it holds. The goal was to study the preliminary National Forest Inventory (NFI) with a special focus on degraded and non-degraded forests. Data was gathered from 25 permanent NFI clusters in the vicinity of Akhmeta in the East of Georgia. As part of the inventory protocol up to 70 variables were recorded, providing complex and integrated information on the available timber as well as ecological characteristics of the forest. No significant differences were found between the degraded and nondegraded forests for the selected variables, canopy cover, regeneration, deadwood, basal area and biodiversity. Nevertheless, the altitude as well as accessibility can give some indication on whether a plot has potential to be degraded or not. The overlap of land-use in the study area made it difficult to distinguish if a stand is degraded or not because of changes in structure and species. Thus, introducing a new variable describing this overlapping area could be a solution for the future. The methodology of the inventory and its sampling design seem sufficient to give general information on the stand; but in this study the results should be understood as indications of the overall condition of the forest, the circumstances under which degradation occurs, and the main causes of degradation in Akhmeta.